Distribution of somatic mutations of cancer-related genes according to microsatellite instability status in Korean gastric cancer - Park, Joonhong (Medicine (Baltimore), 2017)
In studies of the molecular basis of gastric cancer (GC), microsatellite instability (MSI) is one of the key factors. Somatic mutations found in GC are expected to contribute to MSI-high (H) tumorigenesis. We estimated somatic mutation distribution according to MSI status in 52 matched pair GC samples using the Ion Torrent Ion S5 XL with the AmpliSeq Cancer Hotspot panel. Seventy-five (9.8%) somatic variants consisting of 34 hotspot mutations and 41 other likely pathogenic variants were identified in 34 GC samples. The TP53 mutations was most common (35%, 26/75), followed by EGFR (8%, 6/75), HNF1A (8%, 6/75), PIK3CA (8%, 6/75), and ERBB2 (5%, 4/75). To determine MSI status, 52 matched pair samples were estimated using 15 MSI markers. Thirty-nine MS stable (S), 5 MSI-low (L), and 8 MSI-H were classified. GCs with MSI-H tended to have more variants significantly compared with GCs with MS stable (MSS) and MSI-L (standardized J-T statistic  =  3.161 for number of variants; P  =  .002). The mean number of all variants and hotspot mutations per tumor samples only in GCs with MSI-H were 3.9 (range, 1–6) and 1.1 (range, 0–3), respectively. Whereas, the mean number of all variants and hotspot mutations per tumor samples only in GCs with MSS/MSI-L were 1 (0–5)/0.8 (0–1) and 0.5 (0–3)/0.8 (0–1), respectively. In conclusion, GC with MSI-H harbored more mutations in genes that act as a tumor suppressor or oncogene compared to GC with MSS/MSI-L. This finding suggests that the accumulation of MSIs contributes to the genetic diversity and complexities of GC. In addition, targeted NGS approach allows for detection of common and also rare clinically actionable mutations and profiles of comutations in multiple patients simultaneously. Because GC shows distinctive patterns related to ethnics, further studies pertaining to different racial/ethnic groups or cancer types may reinforce our investigations.